Relationships Between the Therapeutic Alliance and Reactions to Artistic Experience With Art Materials in an Art Therapy Simulation - Gazit, Inbal; Snir, Sharon; Regev, Dafna; Bat Or, Michal (Frontiers in Psychology, 2021)
In art therapy, art-making plays an important role in the therapeutic relationship. To better understand the triangular relationship between the art therapist, the client and the artwork, this study investigated the association between the therapeutic alliance and reactions to artistic experiences with art materials in an art therapy simulation. The simulation consisted of a series of 6-8 sessions in which art therapy students were divided into teams composed of a permanent observer (art therapist) and creator (client). The client's role was to self-explore through art- making, and the art therapist's role was to accompany the client. Thirty-four students, all women, who played the art therapist role, and 37 students (one male) who played the client participated in the study. Of these participants, there were 24 pairs where both participants filled out all the questionnaires. A short version of the Working Alliance Inventory (WAI) was completed by the clients and the art therapists on the second session (T1) and on the penultimate session (T2). The clients also completed the Art-Based Intervention Questionnaire (ABI) at T2. Significant positive correlations were found between indices of the WAI for the art therapist and the client and the clients' reactions to the artistic experience with art materials on the ABI. The evaluation of the emotional bond between the art therapist and the client at the start of the simulation significantly predicted the client's reactions to the artistic experience with art materials at the end of the simulation and explained 45.4% of the variance for this variable. These findings highlight factors related to the development and influence of the therapeutic alliance, as well as the role of the artistic experience in art therapy and lay the groundwork for further research.